EFL students - Keke Febrian Harimurti; Yazid Basthomi; Evynurul Laily Zen (Journal on English as a Foreign Language, 2023)
Despite multiple studies that have broadly highlighted the positives of employing metacognitive reading strategies, there remains an absence of the rationale for adopting the reading strategy based on the students' perspectives. The present study aims to look into first-year EFL students' preferences for using metacognitive reading strategies as part of an extensive reading (ER) program at one of the public universities in Malang, Indonesia. The data were acquired from both quantitative and qualitative data sources. The fundamental data were garnered from a quantitative online survey, and the results were counted using descriptive statistics. Semi-structured interview sessions with six participants were carried out to collect qualitative data, and the results served as a means to strengthen the primary data. The results revealed that the problem-solving reading strategy proved to be the most commonly used in the ER program, followed by global and support reading strategies. The reading strategies advanced students' reading comprehension. Students could also strengthen their language skills, particularly reading comprehension, vocabulary acquisition, and writing abilities. The study findings implied considering an alternative teaching strategy and understanding how students find it most helpful to assist them in a supervised ER program.